2000
DOI: 10.1086/317143
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Conditions in a Polar Coronal Hole and Nearby Regions from Norikura andSOHOObservations

Abstract: The distribution of emission-line intensities, Doppler velocities, and line widths in a polar coronal hole and nearby regions are obtained from the spectroscopic observations carried out on 1998 November 3 at the Norikura Solar Observatory, Japan. The coronal red line [Fe X] j6374 that is prominent at coronal hole temperatures is used for the study. The coronal images in Fe IX and Fe X 171 and Fe XII 195 Ó Ó from the Extreme-Ultraviolet Imaging Telescope (EIT) on the Solar and Heliospheric Observatory (SOHO) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 37 publications
(46 reference statements)
3
8
1
Order By: Relevance
“…The results that the line widths are narrower in plumes than in lanes confirm those of Antonucci et al (1997), Hassler et al (1997), Raju et al (2000), and Banerjee et al (2000a), but the difference found is larger than in most earlier studies.…”
Section: Discussionsupporting
confidence: 87%
“…The results that the line widths are narrower in plumes than in lanes confirm those of Antonucci et al (1997), Hassler et al (1997), Raju et al (2000), and Banerjee et al (2000a), but the difference found is larger than in most earlier studies.…”
Section: Discussionsupporting
confidence: 87%
“…Hassler et al (1997), using SUMER data, report a broader line width in interplume regions, with respect to plumes. This result has been confirmed by further studies, from either groundbased coronagraph data (Raju et al, 2000), or from data acquired by space-borne experiments like SUMER (see, e.g., Banerjee et al, 1998Banerjee et al, , 2000b and CDS (see, e.g., Banerjee et al, 2000aBanerjee et al, , 2001O'Shea et al, 2003). A summary of the plume/interplume line widths can be found in Table 2 of Wilhelm (2012).…”
Section: The Plume Effective Temperaturesupporting
confidence: 57%
“…The high speed solar wind outflows are accelerated very close to the solar surface [62]. The solar wind originates from the coronal holes, which are open magnetic field regions with a temperature of ∼ 1 MK [63] (see also ref. [38]).…”
Section: Related Observationsmentioning
confidence: 99%